Evaluasi Tampilan OPAC di Perpustakaan Pusat UIN Maulana Malik Ibrahim Malang - Mufid, Mufid (Pustakaloka, 2012)
The presence of OS (open source) software cause Indonesias higher education libraries strove to produce software. This software provided modules, contaied OPAC. The purposes of this researchÂ  is to evaluate the performance of OPAC in the centre Library of Islamic State University (UIN) Maulana Malik Ibrahim Malang using the standard of IFLA checklist methode. the result is that the OPAC performance of did nit fulfill the standard recommended by IFLA.